The Human Biomonitoring Initiative for Europe (HBM4EU): an overview - Silva, Maria João (2020)
The Human Biomonitoring Initiative (HBM4EU, https://www.hbm4eu.eu/the-project/)) is a Horizon 2020 Framework Project aimed at understanding the European citizens’ exposure to chemical substances from environmental sources, food intake, consumer products or occupational activities. The HBM4EU is organized in three pillars, namely, science to policy, Human Biomonitoring (HBM) platform, and exposure and health, all working to generate harmonised HBM data across the 28 participating countries. To coordinate activities, a National Hub (NH) was established in every country, resulting in the creation of a European HBM network. Following consultation to stakeholders and EU organizations, several substances were prioritized for study, e.g., phthalates, bisphenols, PAHs, cadmium, chromium, mercury, pesticides, and mycotoxins. A chemical group leader (CGL) was assigned to each substance/substance group, to formulate relevant policy questions and propose activities to be undertaken; a Portuguese team is the CGL for mycotoxins. In addition to the analysis of existent data sets for each substance, new and harmonized data on internal exposure to some of them and to mixtures is being produced, which will contribute to fill gaps in knowledge and policy needs. The Portuguese participation in the HBM4EU has allowed to lay the foundations of what could become a wider national HBM network, e.g., by raising awareness of scientists, policy makers and stakeholders about the role of HBM in chemicals risk assessment or contributing to capacity building in some biomarkers analyses. Furthermore, new and comparable data on occupational exposure to hexavalent chromium and on Portuguese population exposure to several chemicals is being generated, which will feed into a pan-European publicly available database. The data will be used to evaluate current chemicals policies and to support the development of new ones, in order to reduce or prevent exposure to hazardous substances and the associated health outcomes, for a healthier future in Portugal and in Europe.